Organizational Diagnosis in Indonesian Manufacturing: A Systematic Review - Tetra Hidayati; Aqiila Tasya Arinanda; Sepriyanti Rombe Layuk; Aulia Safa Firdaus; Adinda Novantri Pamungkas Sari (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesian manufacturing organizations operate in increasingly complex socio-technical environments shaped by structural interdependence, leadership dynamics, cultural norms, and accelerating Industry 4.0 transformation pressures, making organizational diagnosis (OD) essential for identifying systemic misalignment prior to intervention. This study conducts a Systematic Literature Review (SLR) guided by PRISMA 2020 to synthesize peer-reviewed research published between 2012 and 2024 on organizational diagnosis in manufacturing, with particular emphasis on Indonesian contexts. The findings indicate that effective diagnostic practices consistently revolve around four interrelated dimensions: structural alignment, leadership capability, cultural openness, and socio-technical integration. Dominant frameworks include the McKinsey 7S model, the Weisbord Six-Box model, the Burke–Litwin transformational model, Lean-based diagnostics, and socio-technical approaches. The review concludes that integrated and context-sensitive diagnostic strategies, rather than isolated model application, are necessary to enhance transformation readiness, digital adaptation, and long-term organizational resilience in Indonesian manufacturing.